The Effect of Marketing Mix On “KPR Xtra Bebas” Decision Making in Bank X Regional I - Arthur, Kevin Michael; Asmara, Alla; Simanjuntak, Megawati (Journal of Consumer Sciences, 2019)
The rapid growth of mortgages affected Bank X to launch product innovation "KPR Xtra Bebas." Realization since the establishment of KPR Xtra Bebas product did not reach the target desired by management. This study aims to analyze factors that influence consumer decision by using KPR Xtra Bebas products in order to do useful and efficient marketing. Sampling procedure used purposive sampling technique as one of the non-probability sampling techniques, namely sampling based on categories that have used the product. Data used are primary data by filling out the questionnaire conducted by the respondents themselves (self-administered survey). This study used the Partial Least Square (PLS) to analyze results from 94 samples. Results of the study identified the variables of price, place, promotion, and the process did not have a significant influence. While product, human resources, and physical evidence have a significant influence. Managerial implications that are generated are for variables that do not have a significant effect evaluation is needed to determine the appropriate strategy. Companies can build customer databases by implementing cross-selling so that promotional variables can function effectively.